Development Of Fatty Acid-Based Deep Eutectic Solvents In Liquid Phase Microextraction With Back Extraction For Determination Of Selected Organic Pollutants - Sazali, Nur Hidayah (2024)
Environmental pollution has become a significant global issue in recent times. The primary sources of this pollution are human activities such as industrial processes, marine dumping, agricultural practices, and wastewater discharges. Some of the most concerning environmental pollutants are pesticides, herbicides, and polycyclic aromatic hydrocarbons (PAHs) due to their high toxicity and their persistence in the environment. These pollutants have harmful effects on human health and the ecosystem. Due to their high toxicity and trace amount in environment, developing an effective extraction method is essential. Deep eutectic solvent (DES) is a possible green alternative to the conventional solvent utilised in most extraction procedures in light of the increased demand for developing green extraction techniques. Microextraction-based DES fits favourably with the Green Analytical Chemistry (GAC) concept because of its rapid sample preparation time, low organic solvent usage, and straightforward procedure. In this study, an eco-friendly microextraction utilising hydrophobic deep eutectic solvents from fatty acids derived from the combination of lauric acid, which acted as a hydrogen bond acceptor (HBA), and pelargonic acid, which acted as a hydrogen bond donor (HBD), was prepared to determine herbicide mixtures using emulsification liquid-liquid microextraction with back extraction (ELLME-BE) method. In addition, a ferrofluid was developed by incorporating DES, a combination of lauric acid (HBA) and caprylic acid (HBD) with magnetic nanoparticles (MNP) to determine polycyclic aromatic hydrocarbons xxviii (PAHs) using liquid phase microextraction with back extraction (LPME-BE) method. Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA),